UPAYA MENINGKATKAN HASIL BELAJAR DI MASA PANDEMI: MATERI LOMPAT TINGGI GAYA STRADDLE MELALUI LATIHAN SQUAT JUMP - Raden Bagus Budi Rahardja (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This study aims to improve the straddle style of high jump skill through squat jump exercise. This research is a classroom action research, conducted in 2 cycles; each cycle was implemented in three meetings. The subjects were students of class XII SMA IPS 3, SMA N 2 Tarakan with a total of 34. The data in this study are the activities of students and teachers and student learning outcomes. They were collected through observation and skill testing. The researcher was assisted by two fellow teachers who acted as observers. Based on the results of the analysis, it can be concluded that the squat jump exercise can improve students' skills in high jump. The increase can be seen from the pre-action value, and two cycles of action. At first, only 14.71% of students were able to achieve the minimum standard. The percentage was doubled at the end of the first cycle, 35.29%. Their learning mastery get a dramatic spike of almost three times after the second cycle, namely 91.18%, which was also evident from the class average score of 89.95. Thus, this study proves that the squat jump exercise improves students' ability in the high jump.